Beneficial effects of trehalose and gentiobiose on human sperm cryopreservation. - Dariush Gholami; Mohsen Sharafi; Vahid Esmaeili; Touba Nadri; Loghman Alaei; Gholamhossein Riazi; Abdolhossein Shahverdi (PLoS ONE, 2023)
The protection of human sperm during cryopreservation is of great importance to infertility. Recent studies have shown that this area is still a long way from its ultimate aim of maintaining the maximum viability of sperm in cryopreservation. The present study used trehalose and gentiobiose to prepare the human sperm freezing medium during the freezing-thawing. The freezing medium of sperm was prepared with these sugars, and the sperm were then cryopreserved. The viable cells, sperm motility parameters, sperm morphology, membrane integrity, apoptosis, acrosome integrity, DNA fragmentation, mitochondrial membrane potential, reactive oxygen radicals, and malondialdehyde concentration was evaluated using standard protocols. A higher percentage of the total and progressive motility, rate of viable sperm, cell membrane integrity, DNA and acrosome integrity, and mitochondrial membrane potential were observed in the two frozen treatment groups compared to the frozen control. The cells had less abnormal morphology due to treatment with the new freezing medium than the frozen control. The higher malondialdehyde and DNA fragmentation were significantly observed in the two frozen treatment groups than in the frozen control. According to the results of this study, the use of trehalose and gentiobiose in the sperm freezing medium is a suitable strategy for sperm freezing to improve its motion and cellular parameters.